A new frosting map of variable-frequency air source heat pump in severe cold region considering the variation of heating load. (December 2020) - Wei, Wenzhe; Ni, Long; Li, Shuyi; Wang, Wei; Yao, Yang; Xu, Laifu; Yang, Yahua
Abstract: During experiments on investigating the application feasibility of variable-frequency air source heat pump with vapor injection (ASHPVI) in severe cold region, it was found its frosting performance varied significantly from that in former investigations, e.g. in a severe frosting condition (0 °C, 80%), the experimental unit was frost-free. To investigate the frosting characteristics of variable-frequency ASHPVI for space heating in severe cold region, a test rig was built and used to supply heating for a lab in two heating seasons. A new frosting map was developed through summarizing its running performance under frosting condition. Results showed the frosting map of variable-frequency ASHPVI was affected by heating load. Owing to the consideration of heating load, the critical relative humidity decreased from 80.60% to 62.75% when outdoor temperature (OT) dropped from 1.0 °C to −26.5 °C, opposite to the change trend in former investigations. Besides, compared with values obtained in cold region, the upper and lower limits of OT of frosting region in severe cold region were both lower, and its critical relative humidity was higher. Moreover, the highest frosting speed appeared at OT of approximately −10 °C in severe cold region, but not at 0 °C as previously thought. Highlights: A new frosting map considering the variation of heating load was developed. The change trend of critical relative humidity was opposite to the former ones'. The critical relative humidity at 0 °C reached up to 79.25% in severe cold region. The fastest frosting speed in severe cold region appeared at about −10 °C. Heating load had significant influence on frosting performance.